Genetic mechanisms of Escherichia coli resistance to target inactivation. Genes governing purine metabolism in enterobacteria: an unexpected sequence found via complementation selection - Cherepenko, E.; Craig, S. (Биополимеры и клетка, 1997)
Using enierobacterial strains having block in 3 different genes required for GMP synthesis, 3 groups of inserts with different restriction patterns were expected. But the fragments cloned represented 5 such, groups. One consisted of Salmonella typhimurium DNA fragments with 2 SacI sites available. Sequencing revealed 100 % homology of the cloned insert to the N-tenn of Y protein of the hemC-hemD linkage group of E. coli chromosome (85 min locus). It is suggested that Y may represent the gpp gene, coding for guanosinepentaphosphatase. It was also shown that a Salmonella DNA fragment resulting from PCR amplification with 20-mer primers complementary to the N- and C-terms of the hpt gene of E. coli did not encode an hypoxanthine phosplioribosyltransferase (HPRTase)and some other gene complemented GMP synthesis block in tie novo and salvage pathways in E. coli cells. Використання штамів ентеробактерій, які дозволяють клону вати три різних гени шляхів синтезу GMP, надавало мож ливість одержання трьох груп рестрикційних фрагментів. Однак було клоновано п'ять групп таких фрагментів. Фрагменти однієї з цих груп вміщували 2 SacI-сайти, Секвенування фрагмента геному Salmonella typhimurium показало 100 % гомологію з N-кінцем гена Y, який належить оперону hemC-hemD Е. coli. Зроблено припущення, що цей фрагмент вміщує ген, подібний гену gpp Е. coli. Також показано, що фрагмент геному S. typhimurium, який комплементує блок синтезу GMP, ампліфікований у PCR-реакції за. допомогою 20-членних прайме рів до N- та С-кінців гена hpt Е. coli, не кодує HPRT. Использование штаммов энтеробактерий, позволяющих клонировать три различных гена путей синтеза GMP, предполагало получение трех групп рестрикционных фрагментов. Однако были клонированы пять групп таких фрагментов. Фрагменты одной из этих групп содержали 2 SacI-сайта. Секвенирование фрагмента генома. Salmonella typhimurium показало 100 % гомологии с N-концом гена У, принадлежащим оперону hemC-hemD Е. coli Сделано предположение, что этот фрагмент содержит ген, подобный гену gpp Е. coli Также показано, что фрагмент генома S. typhimurium, комплементирующий блок синтеза GMP, амплифицируемый в PCR-реакции с помощью 20-членных прайме ров к N- и С-концам гена hpt Е. coli, не кодирует HPRT.